2017
DOI: 10.1038/nature21411
|View full text |Cite
|
Sign up to set email alerts
|

Complex multi-enhancer contacts captured by genome architecture mapping

Abstract: SummaryThe organization of the genome in the nucleus and the interactions of genes with their regulatory elements are key features of transcriptional control and their disruption can cause disease. We developed a novel genome-wide method, Genome Architecture Mapping (GAM), for measuring chromatin contacts, and other features of three-dimensional chromatin topology, based on sequencing DNA from a large collection of thin nuclear sections. We apply GAM to mouse embryonic stem cells and identify an enrichment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
670
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 618 publications
(693 citation statements)
references
References 64 publications
(102 reference statements)
20
670
0
3
Order By: Relevance
“…This implies that compartmentalization is capable of inducing intrachromosomal loops and interchromosomal links at rapid rates, comparable to those of loop-domain formation. (Our findings may be related to those of other studies, which have noted enhanced interactions between higher-order intrachromosomal interactions between domains containing superenhancers (Beagrie et al, 2017). )…”
Section: Discussionsupporting
confidence: 90%
“…This implies that compartmentalization is capable of inducing intrachromosomal loops and interchromosomal links at rapid rates, comparable to those of loop-domain formation. (Our findings may be related to those of other studies, which have noted enhanced interactions between higher-order intrachromosomal interactions between domains containing superenhancers (Beagrie et al, 2017). )…”
Section: Discussionsupporting
confidence: 90%
“…Such a colocalization of transcribed DNA is supported by recent studies of DNA-DNA contacts. For example, DNA-DNA contacts are significantly enriched in highly transcribed DNA elements (Rao et al, 2014;Beagrie et al, 2017), transcription levels predict DNA-DNA contact frequencies (Rowley et al, 2017), and long-range DNA-DNA contacts depend on ongoing transcription (Hug et al, 2017). At the megabase scale, the genome can be assigned to regions that are defined by an elevated internal contact frequency (Lieberman-Aiden et al, 2009).…”
Section: Microenvironments Might Explain Major Features Of Genome Arcmentioning
confidence: 99%
“…In addition to affecting the degree of chromatin compaction, transcription has long been suggested to result in DNA-DNA contacts (Cook, 1999). Indeed, genome-wide analyses of DNA-DNA contacts have revealed that transcribed elements are enriched amongst these contacts (Beagrie et al, 2017;Rowley et al, 2017). Moreover, long-range contacts between transcribed regions are lost when transcription is inhibited (Schoenfelder et al, 2010;Hug et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, transcriptionally active regions are often co-localised in super-enhancer hubs [8] or transcription factories [14], whereas transcriptionally inactive regions may form large heterochromatic foci [15], mega-base (Mbp) size lamin-associated domains [16] or Barr [17] and Polycomb bodies [18].…”
Section: Introductionmentioning
confidence: 99%
“…The epigenetic patterning of chromatin -the fibre made of DNA wrapped around histone proteins [1] -has been shown to strongly correlate with the three-dimensional (3D) nuclear organisation of interphase chromosomes [7][8][9][10][11][12][13]. For instance, transcriptionally active regions are often co-localised in super-enhancer hubs [8] or transcription factories [14], whereas transcriptionally inactive regions may form large heterochromatic foci [15], mega-base (Mbp) size lamin-associated domains [16] or Barr [17] and Polycomb bodies [18].…”
Section: Introductionmentioning
confidence: 99%